2015
DOI: 10.1016/j.jpedsurg.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of intestinal tissue engineering combined with Bianchi’s procedure

Abstract: SIS has the potential for use as a scaffold that promotes the formation of a physical and physiological neointestine. Our present proposal approaches a novel surgical treatment in patients with short bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…The third limitation is the lower force generated by our engineered tissues compared to native rat intestines. A recent study reported force values generated by an implanted engineered intestine to be one-fourth of native intestine [36]. The forces generated by our engineered tissues were 50%-70% those of the native intestine.…”
Section: Discussionmentioning
confidence: 84%
“…The third limitation is the lower force generated by our engineered tissues compared to native rat intestines. A recent study reported force values generated by an implanted engineered intestine to be one-fourth of native intestine [36]. The forces generated by our engineered tissues were 50%-70% those of the native intestine.…”
Section: Discussionmentioning
confidence: 84%
“…Even though the forces generated by the engineered complexes were lower than the forces generated by the native intestine, it is important to note that the force patterns displayed by the engineered complexes are similar to those of native tissues (Zakhem, Elbahrawy, Orlando, et al, , b). Engineered gut tissues generating lower force than native gut tissues has also been a challenge in other studies (Nakao et al, ). In future studies involving anastomosis of the engineered complexes to native intestines, it will be interesting to evaluate whether host cells infiltrate the engineered tissues and increase the magnitude of force generated by the engineered tissues.…”
Section: Discussionmentioning
confidence: 99%
“…SIS was previously used as a patch to repair an intestinal defect. [14] Follow-up studies using SIS as a tubular structure to repair the defect are needed. Urinary bladder matrix promoted epithelial regeneration by attracting bone-marrowderived cells to the site of injury.…”
Section: What Type Of Matrix Can Be Used As Support For the Cells?mentioning
confidence: 99%